The effectiveness of surca for land surveyor in Kemaman - Mohamad Hafiz Che Awang
The interests of land are managed and governed through the process of land management and the administrative system operated through legal and institutional frameworks. Land administration is part of land management and it includes public sector activities that facilitate and assist the process of segregation, allocation, survey, a sessment, registration, transfer, development, and land use. Other than ensuring people to easily access to land, effective land management processes also drive growth through increa ed investment. One of the ways whereby land resources are being put to the highest and best use is through application development in land management. This study was conducted to investigate the management approach adopted by the Kemaman District Land Office in Terengganu in the application of SurCa applications in each land-use mix as well as to evaluate the effects of management approach on the land development application process. The conceptual framework of this tudy based on objective management theory (MBO) is a management approach that supports the measurable objective specification, set goals, participatory approaches, and feedback systems. Random sampling techniques were applied to look at the use of SurCa applications in land development that will be analyzed in thi study. tudie have shown that no performance control measures or other age and important factors found to be important to the field in the use of urea applications. With regard to assessing the impact of the management approach on the SurCa application process, the study found that users and employees expressed interest and need in using the SurCa application to facilitate their business and expedite bu ines management. Despite some of the constraints inherent in this study, the application requirements of this SurCa application should be expanded either in the state of Terengganu or throughout Malaysia for the countr to become more prosperous in the future.